Influence of Workplace Ostracism on Workplace Behavior: The Moderating role of Neuroticism (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This study explores the relationship between  workplace ostracism and workplace behavior,  with a focus on how neuroticism moderates  this relationship. Data from 100 employees in  private firms in India were analyzed using PLS SEM. Results indicate that workplace ostracism  negatively impacts job performance but not  deviant behavior. Neuroticism has a stronger  moderating effect on the link between workplace  ostracism and job performance but does not  affect deviant behavior. The study contributes  to existing knowledge by examining the  moderating effect of neuroticism on workplace  exclusion
Keywords: Workplace Ostracism; Job Performance; Deviant Behaviour; Neuroticism; COR (Conservation of Resource)Theory